(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
The fast-paced growth coupled with the global acceptance of cloud computing has significantly changed how information technology is viewed. The advantages presented in scale, cost and operations have never been experienced before. Nevertheless this change has also created another layer of issues that organizations need to deal with full scale in order to protect their cloud resources against unauthorized access, use and destruction. This long and detailed essay includes review of numerous threats, solutions and best practices regarding cloud computing security. This study is based on an understanding of cloud security at present by employing qualitative and quantitative methods. For example, the first 1000 security incidents were evaluated; surveys of 500 IT security experts and 50 industry leaders were conducted. The analysis showed that the cloud security landscape is becoming complex, and while the security technologies and practices have progressed tremendously, there are challenges still persistent. According to the research, physical security controls are in place for 76% of organizations practicing multi-factor authentication, yet only 68% have supplied and implemented an all-inclusive cloud security plan, a disturbing discrepancy in the organizations’ approaches to security [1]. The research not only identifies and examines these issues but also offers practical suggestions and looks at the technologies that will influence cloud computing security in the years to come, therefore answering the questions posed by both academics and practitioners